The antibacterial and antibiofilm potential of Paederia foetida Linn. leaves extract - Jepri Agung Priyanto, Muhammad Eka Prastya, Genia Sotya Sinarawadi, Wani Datu’salamah, Theresia Yolanda Avelina, Ai Ika Ayu Yanuar, Elaeisa Azizah, Zetryana Puteri Tachrim, Tjandrawati Mozef (Journal of Applied Pharmaceutical Science, 2022)
Paederia foetida is one of Asia’s native plants which is traditionally used for medicinal purposes. The antibacterial and antibiofilm properties of this plant, as well as the identification of its active fractions, have been evaluated in this study. The methanolic extract of dried P. foetida leaves showed antibacterial activity against Escherichia coli and Mycobacterium smegmatis with clear zone diameters of 26 ± 1.4 and 37.6 ± 0.41 mm, respectively, as assessed by the disk diffusion method. Six fractions have been separated using thin-layer chromatography. Of the six fractions tested, two fractions (F5 and F6) possessed antibacterial properties against two tested bacteria. These two fractions have lower minimum inhibitory concentration (MIC) and minimum bactericidal concentration values than those of the crude extract, ranging from 23.43 to 125 μg/ml. More than 50% of M. smegmatis biofilm and 30% of E. coli biofilm formation have been inhibited by the extract and active fractions of this plant. Moreover, two MIC of the extract and fractions were also able to destroy the established biofilm mass of the tested bacteria. As identified using LC-MS/MS, the F5 and F6 fractions have different major components. Linolenic acid, carotenoid, and icosanamide were detected in the F5 fraction. Furthermore, phaeophytin A was detected in the F6 fraction.
Keywords: Antibacterial, antibiofilm, Escherichia coli, Mycobacterium smegmatis, Paederia foetida, leaves extract